Scientific literacy and science learning achievement at junior high school - Jufrida Jufrida; Fibrika Rahmat Basuki; Wawan Kurniawan; Miko Danu Pangestu; Olva Fitaloka (Institute of Advanced Engineering and Science, 2019)
Scientific literacy is the ability which must be owned by the students to analyze and apply the concept of science in solving daily life problem. This research aims to know the correlation between scientific literacy and science learning achievement at State Junior High Schools. This research used a quantitative approach with correlational type. The population of this research were 428 grade IX students at State Junior High Schools within the District of Jaluko Muaro Jambi. The samples was 138 students. The technique of selecting samples was random sampling. The instruments used were the test of science literacy and the test of science learning achievement. Hypothesis test was conducted by using rank spearman correlation test with the assistance of SPSS 21. The results show the average score of scientific literacy is 33.7 (medium category) and the average score of science learning achievement is 21.5 (very low category). The result of the correlation test obtains Sig value 0.00 then Ho is rejected. It can be concluded that there is a significant correlation between scientific literacy and science learning achievement at State Junior High School within Muaro Jambi District. Science learning is expected to develop students’ science literacy so that it can improve science learning achievement.